Meningkatkan Pendapatan Masyarakat Kelurahan Leksono Melalui Pengelolaan Sampah Non-Organik Menjadi Kerajinan Tangan - M. Trihudiyatmanto; M. Elfan Kaukab; Nada Maulida T; Eka Prihati; Occa Hafidz A; Jumaidi Jumaidi; Rasyid Fadillah; Mustofa Mustofa; Ainun Nafisatul A; Kholishotul H; Fatoni Fatoni; Marlia Nurhayati; Aditya Kusuma (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2023)
Garbage is still a strategic issue in almost every region, including Leksono Village Area, Leksono District, Wonosobo Regency. There's a lot of trouble with garbage that hasn't found a bright spot, one of them is a good way of handling it. That sounds cliché, but that's what's happening on the ground. The aim of this program is to increase the creativity and productivity of the community; hopefully, the community can manage and use their non-organic garbage in handicrafts so that they can later have a sales value. The research uses a qualitative approach with descriptive methods, which aims to describe the management of garbage so that it can improve the well-being of the community. The program is put into action by inviting and organizing the residents of Leksono to separate their garbage into organic and non-organic categories, with the non-organic waste then being used for handicrafts. With the implementation of these activities, waste treatment residues can be stored and well utilized.